2017
DOI: 10.1007/s10552-017-0914-y
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic disparities in survival for adolescents and young adults with cancer differ by health insurance status

Abstract: Purpose To investigate associations of sociodemographic factors—race/ethnicity, neighborhood socioeconomic status (SES), and health insurance—with survival for adolescent and young adults (AYAs) with invasive cancer. Methods Data on 80,855 AYAs with invasive cancer diagnosed in California 2001–2011 were obtained from the California Cancer Registry. We used multivariable Cox proportional hazards regression to estimate overall survival. Results Associations of public or no insurance with greater risk of deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 51 publications
3
47
0
Order By: Relevance
“…55 Lower neighborhood SES was associated with a greater risk of death in AYAs who had private insurance and in those aged 25 to 34 years regardless of insurance type. 55 For sur vivors, cancerrelated financial concerns can affect future health care, making patients more likely to delay or forgo medical care. 56 In the AYA population, 24% of cancer survi vors report forgoing medical care because of cost, compared with 15% of those with no history of cancer.…”
Section: Health Insurance and Socioeconomic Statusmentioning
confidence: 94%
See 2 more Smart Citations
“…55 Lower neighborhood SES was associated with a greater risk of death in AYAs who had private insurance and in those aged 25 to 34 years regardless of insurance type. 55 For sur vivors, cancerrelated financial concerns can affect future health care, making patients more likely to delay or forgo medical care. 56 In the AYA population, 24% of cancer survi vors report forgoing medical care because of cost, compared with 15% of those with no history of cancer.…”
Section: Health Insurance and Socioeconomic Statusmentioning
confidence: 94%
“…There is evidence supporting a relationship between poverty and decreased access to health care, poorer health care utilization, and inferior patient outcomes in multiple medical conditions, including cancer . An association between neighborhood SES and survival has been demonstrated in AYAs with leukemia, lymphoma, melanoma, breast cancer, and colon cancer . Lower neighborhood SES was associated with a greater risk of death in AYAs who had private insurance and in those aged 25 to 34 years regardless of insurance type .…”
Section: Improving Outcomes Of Ayas With Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cancer type and cancer treatment-related exposures (9,10), sociodemographic characteristics may also be important predictors of noncancer health outcomes among AYAs with cancer in the United States Reports from California have demonstrated disparities in all-cause and cancer-specific mortality among AYA cancer survivors according to race/ethnicity and arealevel socioeconomic status (SES; refs. [11][12][13][14][15]. However, the longterm risk of mortality from noncancer causes, such as cardiovascular diseases (CVD) and infectious diseases (ID), according to race/ethnicity, SES, and other factors has not been described in the AYA cancer survivor population.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent report from the Centers for Disease Control and Prevention found increased mortality among Blacks compared to other racial groups for all age ranges under 65 though this gap had narrowed recently [33] and a study by Yen et al showed that decreases in lupus mortality over the last 46 years were slower in Blacks individuals compared to White individuals [34]. Among adolescents with cancer, an increase in mortality rates among African Americans was found to be mainly associated with insurance status and socioeconomic status [35] which also seemed to be at play in our study though it was not significant and not included in the final model. While the odds of inpatient mortality in Black race individuals improved when controlling for insurance status and income quartile of ZIP code, increased odds of death did still persist.…”
Section: Discussionmentioning
confidence: 97%